Construction of an evaluation index system for development level of county-level chronic disease management centers: a Delphi study - Xiaoyong HE; Fan MAO; Lingzhi KONG; Run ZHANG; Shiqiang FENG; Xiaoqing YOU; Jianhong LI (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo construct an evaluation index system for the development level of county-level chronic disease management centers, providing a basis for evaluating and comparing the construction of these centers. MethodsFocusing on the key points of county-level chronic disease management center construction and combining relevant literature, a candidate index database was constructed. Twenty-nine experts in the field of chronic disease management were selected to conduct two rounds of Delphi consultation to determine the evaluation index system for the development level of county-level chronic disease management centers, and the analytic hierarchy process was used to determine the index weights. ResultsThe active participation rates of experts in the two rounds of Delphi consultation were 90.91% and 96.67%, respectively, with expert authority coefficients of 0.85 and 0.84, and Kendall's W of 0.15 and 0.20 (both P < 0.001). After two rounds of consultation, a final evaluation index system for the development level of county-level chronic disease management centers was constructed, consisting of 5 dimensions and 45 indicators: organizational management and basic conditions, chronic disease management informatization, county-township collaborative management of chronic diseases, capacity building and quality control of chronic disease management, and quality and effectiveness of chronic disease management. The weights of the 5 dimensions were 0.212 2, 0.180 1, 0.219 4, 0.179 4, and 0.208 9, respectively. ConclusionThe evaluation index system for the development level of county-level chronic disease management centers constructed in this study is reasonable, practical, representative, and instructive, providing a reference basis for evaluating the development level of these centers and key directions for subsequent construction.